Differentiating Botulinum Neurotoxin-Producing Clostridia with a Simple, Multiplex PCR Assay - Williamson, Charles H. D. (Appl Environ Microbiol, 2017)
Diverse members of the genus Clostridium produce botulinum neurotoxins (BoNTs), which cause a flaccid paralysis known as botulism. While multiple species of clostridia produce BoNTs, the majority of human botulism cases have been attributed to Clostridium botulinum groups I and II. Recent comparative genomic studies have demonstrated the genomic diversity within these BoNT-producing species. This report introduces a multiplex PCR assay for differentiating members of C. botulinum group I, C. sporogenes, and two major subgroups within C. botulinum group II. Coding region sequences unique to each of the four species/subgroups were identified by in silico analyses of thousands of genome assemblies, and PCR primers were designed to amplify each marker. The resulting multiplex PCR assay correctly assigned 41 tested isolates to the appropriate species or subgroup. A separate PCR assay to determine the presence of the ntnh gene (a gene associated with the botulinum neurotoxin gene cluster) was developed and validated. The ntnh gene PCR assay provides information about the presence or absence of the botulinum neurotoxin gene cluster and the type of gene cluster present (ha positive [ha(+)] or orfX(+)). The increased availability of whole-genome sequence data and comparative genomic tools enabled the design of these assays, which provide valuable information for characterizing BoNT-producing clostridia. The PCR assays are rapid, inexpensive tests that can be applied to a variety of sample types to assign isolates to species/subgroups and to detect clostridia with botulinum neurotoxin gene (bont) clusters. IMPORTANCE Diverse clostridia produce the botulinum neurotoxin, one of the most potent known neurotoxins. In this study, a multiplex PCR assay was developed to differentiate clostridia that are most commonly isolated in connection with human botulism cases: C. botulinum group I, C. sporogenes, and two major subgroups within C. botulinum group II. Since BoNT-producing and nontoxigenic isolates can be found in each species, a PCR assay to determine the presence of the ntnh gene, which is a universally present component of bont gene clusters, and to provide information about the type (ha(+) or orfX(+)) of bont gene cluster present in a sample was also developed. The PCR assays provide simple, rapid, and inexpensive tools for screening uncharacterized isolates from clinical or environmental samples. The information provided by these assays can inform epidemiological studies, aid with identifying mixtures of isolates and unknown isolates in culture collections, and confirm the presence of bacteria of interest.